JADID NAMOYANDALARI ASARLARIDA ILM VA MA’RIFAT TALQINI - Axrorova, M. (SCIENCE and SOCIETY, 2024)
The article talks about the promotion of knowledge and enlightenment in the works of Alisher Navoi and the representatives of Jadid, and the fact that ignorance is a tool that leads to ignorance, and it is analyzed on the basis of examples.